Pharmacokinetics of Intravenous and Oral Phenobarbital Sodium in Healthy Goats - Yates, Liana M.; Aleman, Monica; Knych, Heather K.; Knipe, Marguerite F.; Crowe, Chelsea M.; Chigerwe, Munashe (Frontiers in Veterinary Science, 2020)
Phenobarbital is a common drug used to manage epilepsy in goats. However, the recommended dose and dosing frequency are based on studies in dogs and horses. Studies describing the pharmacokinetics of phenobarbital when administered orally and assessing changes in behavior with concurrent electroencephalogram (EEG) readings are warranted in goats. The objectives of this study were to determine the bioavailability of orally administered phenobarbital and determine the effect of phenobarbital on brain activity using EEG in healthy goats. A cross-over design with 8 non-pregnant goats was performed. The goats were administered phenobarbital intravenously at 10 mg/kg, followed by a 2 week wash out period, and then administered phenobarbital, orally, at 10 mg/kg. Plasma sample determination of phenobarbital concentrations were collected at 13 time points. Continuous EEG readings with simultaneous video recording for 12 hours was performed to determine the state of vigilance using a behavior scoring system prior to and after phenobarbital administration. Bioavailability of phenobarbital was 24.9%. Mean ± SD for half-life was similar between the oral (3.80 ± 0.826 hours) and intravenous (4.0 ± 0.619 hours) routes. Time to observed maximum concentration (Tmax), and maximum plasma concentration (Cmax) for the oral administration were 1.75 ± 0.46 hours, and 4,478.7 ± 962.4 ng/mL, respectively. Clearance was 152.5 ± 102.7 ml/h/kg. Area under the curve from zero to infinity (AUC0  ∞) was 155,813 ± 218,448 and 38,763 ± 9,832 h*ng/mL for the intravenous and oral administration routes, respectively. Behavior score at 3 hours after phenobarbital administration was different (P = 0.0002) from the score prior to administration for the oral administration route. In contrast, behavior scores before administration of phenobarbital and each time point after administration were not different (P >0.05) for the intravenous administration route or other oral administration route time points. Bioavailability of phenobarbital was poor, and the half-life was very short due to a high clearance. Doses greater than 10 mg/kg should be considered when phenobarbital is administered orally in goats.